PEMETAAN STRUKTUR LUAR KAMPUNG KOTA TANJUNG GEDONG - Fermanto Lianto; Rudy Trisno; Mieke Choandi; Denny Husin (Jurnal Bakti Masyarakat Indonesia, 2021)
Kampung Tanjung Gedong is located at Tanjung Gedong lane. It is situated at the back of the educational area in Grogol, West of Jakarta. This kampung area is surrounded by the city’s facilities, like the University of Tarumanagara, the University of Trisakti, the Sumber Waras Hospital, other residential and commercial areas. In terms of the urban fabric, this kampung is characterized by irregularity and informality. Its streets are varied in size, meandering in shapes and forming a semi-labyrinth environment. Its inhabitants are students, laborers, street vendors, traders, etc. Despite having moderate spatial quality, Kampung Tanjung Gedong requires an improvement to be able to adapt to its context. One of the most effective solutions is to improve the condition by providing its inhabitants with education. Related to architecture, a community engagement project is planned to transfer knowledge by using mapping as training. It is intended to stimulate a better understanding of its inhabitants regarding the potency of the space. The activity includes documentation, both as actualization and archive. The methods are manual and digital mappings, it is a combination of hand and digital sketching by using manual tools and digital instruments. The mapping process is supported by Autodesk cad and camera as the tools. Drawing in this sense is utilized as a media for discussion and presentation. The finding is a cross-checking method, re-examination as a process to re-check existing location against archive and photography. The result is a series of manual, digital, and graphic mappings of kampung Gedong’s surface structureABSTRAK:Kampung Tanjung Gedong terletak di jalan Tanjung Gedong, berlokasi di belakang kawasan pendidikan Grogol Jakarta Barat. Dikeliling parsel-parsel kawasan pendidikan, seperti: Universitas Tarumanagara, Universitas Trisakti, Rumah Sakit Sumber Waras dan area komersial di sekitarnya; kampung Tanjung Gedong merupakan area pendukung yang menyediakan kebutuhan kawasan sekitar. Kampung ini karakteristik tidak beraturan, dengan kondisi rumah yang tidak selalu tertata. Kondisi jalan bervariasi dengan gang-gang yang berkelak-kelok. Pekerjaan penghuninya bervariasi dari: pekerja, mahasiswa, pedagang informal dan sebagainya. Meski hidup rukun dan damai, kondisi lingkungan dan ruang hidup mereka perlu terus ditingkatkan agar dapat beradaptasi dengan kemajuan jaman, salah satunya dengan transfer keilmuan tentang keruangan melalui pemetaan yang dapat memberikan pemahaman atas potensi ruang dan lingkungan tempat tinggal mereka. Selain itu, pemetaan berguna sebagai dokumentasi sebagai aktualisasi peta eksisting karena transformasi struktur kampung yang cepat. Pemetaan dilakukan dengan metode manual, yakni: sketsa menggunakan pola dan metode tracing dan digital menggunakan autodesk cad. Gambar adalah bahasa komunikasi pada sebuah lokasi sampel, sebuah hasil observasi, diskusi dan dokumentasi. Tujuannya kegiatan dalah memanfaatkan proses menggambar menjadi sarana pelatihan, sementara hasil akhir sebagai visualisasi yang berguna sebagai dokumentais. Temuannya adalah kedua metode saling melengkapi sebagai alat pertukaran informasi, dan memungkinkan pemeriksaan kembali (cross-checking) pada proses pemetaan. Hasil akhir berupa peta manual, pola pemetaan, peta digital dan peta grafis untuk mempresentasikan keruangan kampung.